PENGELOMPOKAN KABUPATEN/KOTA DI JAWA TIMUR BERDASARKAN PROGRAM PELAYANAN KESEHATAN IBU - Ainun Nufus (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2019)
Maternal health services are one of the basic health efforts that must be carried out by the local government. Good maternal health services affect the degree of maternal health. Maternal health degrees are measured by the Maternal Mortality Rate (MMR). One of the cases is the increasing return of MMR in East Java Province in 2016. The main causes of high MMR in East Java are bleeding and preeclampsia. Local governments try to reduce MMR by optimizing maternal health care efforts in various work areas. The purpose of this study is to apply the analysis of cluster complete linkage to describe the distribution of areas of achievement of maternal health care programs in East Java Province in 2016. The data used in the analysis of cluster complete linkage is the scale of data ratios. This type of research is non-reactive using secondary data. The data used in this study is the maternal health service profile data obtained from the program planning and budget sub-section of the East Java Provincial Health Office in 2016. The results of cluster analysis research were conducted to produce 2 optimum districts clusters, with the highest statistical pseudo-f value of 92,420. Cluster 1 produced 4 district members, while Cluster 2 produced 34 members. The conclusion of this study shows that between cluster 1 and cluster 2 has different characteristics. The naming of each cluster is based on the characteristics of the average value of the achievement of the maternal health care program. Cluster 1 is a group of districts whose program achievement status is below the target, while Cluster 2 is a group of districts whose program achievement status is above the target.